2020
DOI: 10.1097/acm.0000000000003077
|View full text |Cite
|
Sign up to set email alerts
|

Seeking Inclusion Excellence: Understanding Racial Microaggressions as Experienced by Underrepresented Medical and Nursing Students

Abstract: Policy Foundations for Medical Schools, is the second edition of the first Roadmap publication in the series that addresses enrollment and admission issues related to holistic review, student diversity, and evaluation. Produced by the AAMC Advancing Holistic Review Initiative, this document has been developed to help medical schools establish and implement institution-specific, diversityrelated policies that will advance their core educational goals with minimal legal risk. It includes new guidance associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
93
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 135 publications
(95 citation statements)
references
References 11 publications
2
93
0
Order By: Relevance
“…The electronic mailing list for the AAMC Group on Diversity and Inclusion has recently seen many inquiries by members seeking tools to teach this content at their institutions. Given the primary author's expertise in microaggressions in health professions students 1 and the authors' development of the Microaggressions Triangle Model, 4 a humanistic model to respond to microaggressions, we sought to fill the gap in the literature with this workshop. It was first created to be used at monthly lunch-and-learn diversity dialogues as a method for helping medical students to recognize and understand the nature of microaggressions and how to respond to them.…”
Section: Introductionmentioning
confidence: 99%
“…The electronic mailing list for the AAMC Group on Diversity and Inclusion has recently seen many inquiries by members seeking tools to teach this content at their institutions. Given the primary author's expertise in microaggressions in health professions students 1 and the authors' development of the Microaggressions Triangle Model, 4 a humanistic model to respond to microaggressions, we sought to fill the gap in the literature with this workshop. It was first created to be used at monthly lunch-and-learn diversity dialogues as a method for helping medical students to recognize and understand the nature of microaggressions and how to respond to them.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrated that undergraduate nursing students often encounter emotional problems due to academic stress [18,5]. The underlying stressors include frequent academic assessment and disparity between academic studies and medical practice, which often will affect the outcome of nursing training.…”
Section: Discussionmentioning
confidence: 99%
“…25 Without adequate exposure to faculty like themselves, URiM students may not receive the role-modeling needed to cultivate their aspirations. 26,27 Similarly, overemphasis on clinical grading and honors, which has been shown to be discriminatory, impacts URiM students' ability to be competitive in their residency applications. 24,[28][29][30] On the Medical Student Performance Evaluation (MSPE), Black medical students are more frequently described as "competent," which is less likely to have positive connotation for Black students, in comparison with their white counterparts who are more likely to be described as "outstanding" or "exceptional."…”
Section: Racism In Medical Education Todaymentioning
confidence: 99%
“…White faculty should call out microaggressions and discrimination in the educational environment. 26,27,52 Learner Support and Academic Environment…”
Section: Professional Culturementioning
confidence: 99%